Effect of medical insurance policy on child health indicators: an empirical test of difference-in-differences model - Hui Luo; Jiechuan Fu; Mimi Xiao (Frontiers in Public Health, 2025)
BackgroundThe integration policy of urban and rural medical insurance of China is an important policy benefiting the people, aimed at promoting health equity and improving the level of medical security. In the present analysis, we aimed to identify the association between health policy implementation and child health taking China for example.MethodsData were drawn from the child sample of China Family Panel Studies (CFPS) 2012–2018, totaling 11,003 items, and the number of illness times, height-for-age Z-score, weight-for-age Z-score and BMI-for-age Z-score were served as health indicators. This paper used the difference-in-differences model to explore the impact of urban and rural medical insurance integration policy on children’s health and the moderating effect model to analyze the mechanism of action.ResultsOur study found that urban–rural medical insurance integration has a positive impact on reducing children’s illness and improving nutritional status, particularly among middle socioeconomic status and rural children. In provinces that implemented the policy in 2017, the realization of the integration policy decreased the number of times of children getting sick (β = −0.097, p < 0.05), and increased the BMI-for-age Z-score (β = 0.194, p < 0.05). In addition, participation in commercial medical insurance enhanced the positive impact of the integration of urban and rural medical insurance on children’s physical fitness. However, in provinces that implemented the policy in 2018, policy implementation did not change any health indicators. This may suggests a trend where the health promotion effect of the integration policy gradually emerged over time.ConclusionIt is hoped that this study will provide a policy basis and institutional reference for policy makers to construct and develop the children’s health insurance system.